PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PREZI TERHADAP HASIL BELAJAR IPS : Studi Eksperimen Pada Siswa Kelas VIII SMP Negeri 150 Jakarta - Kurniawan, Fajar; Budiaman, Budiaman (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
This research aims to find out whether the use of learning media Prezi affect social studies learning results. This research done in the SMP 150 Jakarta with a sample of the class VIII Research samples taken by purposive random sampling with random sampling but with specific considerations. The research method used is a quasi experimental method is to know the influence of the treatment (treatment) that is done in the form of the use of learning media Prezi on the outcome of the Social Studies learning. Data collection techniques by doing the initial test (pretest) and test the end (posttest). After the collected data the next step test analysis prerequisites continued with the hypothesis test. Based on the analysis of the end of that has been done with test normalitas using test homogenitas liliefors tests and with using the fisher test shows that the two samples from the population that berdistribusi normal and homogeneous. The research results showed that the value is greater than ttabel thitung (3,746 > 1,997) on KD 6.3 control of Social Deviance and that the value is greater than ttabel thitung (3,043 > 1,997) which means the hypothesis Ha accepted. The average grade student learning outcomes experiment the use of learning media prezi higher compared with an average of the results of learning control classes using powerpoint. This can be seen from the number of students who are interested and active in the learning process after given treatment by using media Prezi so that the learning results obtained both. The conclusion of this research is the use of learning media Prezi have a significant influence on the outcome of the Social Studies learning on the students of class VIII in the SMP 150 Jakarta.